Morfodinâmica e transporte fluvial no Sudoeste do Estado do Paraná por método de levantamento de microbacias hidrográficas através de geoprocessamento - Tomazoni, Julio Caetano (2003)
In the Southwest area of the Paraná state, in the rural area, the relevant environmental problems concentrate on the degradation of the pedologic covering and on the eradication of the natural vegetable covering, due to inadequade agricultural use that accelerates the hydric erosion polluting rivers with particulated material and agricultural fertilizers and pesticides. To give a perspective of solving these problems, it was developed a study that has the purpose of contributing with the administration methods and environmental monitoring of watersheds within an integrated vision of the morphodynamic and fluvial transport. To the execution of the works, it was selected the watersheds of the rivers Anta Gorda in Santa Isabel do Oeste country, Brinco in Clevelândia country, Coxilha Rica in Itapejara D’ Oeste country and Jirau in Dois Vizinhos country, all in the Southwest of Paraná State. These basins are located at strategic places, with differentiated physical characteristics, mainly regarding to soil, climate and geomorphology. The hydric enviroment was evaluated by the quantification of the particled flows and dissolved material transported and by the rescue of historical data of Parana Sanitation Company - SANEPAR. Besides, it was obtained the medium factor 0,6937 for conversion of the turbidity in Nefelometric Turbidity Unit - NTU for particled material in mg/L. It was developed a methodology in software SPRING ambient that uses the factors of Universal Loss Equation (USLE) and the tolerable losses for each type of soil to determine the use capacity classes for the pedologic covering of each basin and then to identify the most appropriate conservationists practices.